(untitled) (World Economics and Finance Bulletin, 2023)
The most controversial accounting standard of the past decade, IAS 39 Financial Instruments: Recognition and Measurement, and its American equivalent FAS 133 Derivative Instruments and Hedging Activities” and FAS 157 “Fair Value Measurements” have regained their status as a global focus of public debate since the beginning of the current crisis. After recent harsh criticism, standard-setters have launched several targeted projects in considering accounting issues arising from the crisis. The result so far is Publishing of IFRS 9 Financial Instruments issued by the IASB and Exposure Draft on Financial Instruments issued by the FASB. Bankers and companies facing huge challenges in understanding and applying the International Financial Reporting Standard 9 Financial Instruments (IFRS 9). This lack of understanding opens the horizons of doubts and this study examines the International Financial Reporting Standard 9 Financial Instruments (IFRS 9) to facilitate its understanding, value and application for bankers. Furthermore, one of the major tools that the study used is the historical proactive to attain a better recognition and application of the (IFRS 9)